ENFORCEMENT OF REGIONAL REGULATION NUMBER 5 OF 2020 CONCERNING STANDARDS FOR THE IMPLEMENTATION OF BALINESE CULTURAL TOURISM (CASE STUDY OF ILLEGAL TOUR GUIDES IN THE TANJUNG BENOA REGION, SOUTH KUTA DISTRICT, BADUNG REGENCY) - I Putu Arik Sanjaya; I Wayan Wesna Astara; Luh Putu Sudini (NOTARIIL Jurnal Kenotariatan, 2023)
This research analyzes the enforcement of Regional Regulation Number 5 of 2020 Concerning the implementation of Balinese cultural tourism in the Tanjung Benoa area, South Kuta District and to find out legal remedies related to the existence of illegal tour guides in the Tanjung Benoa area, South Kuta District. The problems in this study, (1) how enforcement of Regional Regulation Number 5 of 2020 concerning Standards for the Implementation of Balinese Cultural Tourism in the region Tanjung Benoa South Kuta District and (2) What are the legal remedies related to illegal tour guides in the Tanjung Benoa area, South Kuta District. This study uses empirical legal research methods, with a statutory, conceptual and case approach, then analyzed qualitatively descriptively. The enforcement of Regional Regulation Number 5 of 2020 Concerning Standards for the Implementation of Balinese Cultural Tourism in the Tanjung Benoa area, South Kuta District, has been running effectively. It can be proven by cooperation between the relevant government and the community to reduce the activities of illegal tour guides who can provide inaccurate information to tourists about tourist attractions in the Tanjung Benoa area. Then legal remedies that can be taken are carrying out raids in tourist destinations, providing coaching in the form of verbal warnings also summons by making a written statement not to carry out illegal tour guide activities and giving sanctions that are adjusted to the applicable laws and regional regulations are a form of law enforcement.